2017
DOI: 10.1371/journal.ppat.1006280
|View full text |Cite
|
Sign up to set email alerts
|

The redefinition of Helicobacter pylori lipopolysaccharide O-antigen and core-oligosaccharide domains

Abstract: Helicobacter pylori lipopolysaccharide promotes chronic gastric colonisation through O-antigen host mimicry and resistance to mucosal antimicrobial peptides mediated primarily by modifications of the lipid A. The structural organisation of the core and O-antigen domains of H. pylori lipopolysaccharide remains unclear, as the O-antigen attachment site has still to be identified experimentally. Here, structural investigations of lipopolysaccharides purified from two wild-type strains and the O-antigen ligase mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 56 publications
(103 reference statements)
4
81
1
1
Order By: Relevance
“…Furthermore, the crystal structure of H. pylori HldD revealed that both the substrate binding site and the overall structure were highly similar to those of the HldD of E. coli , suggesting a conserved enzymatic function ( 36 ). It has also been shown that deletion of several enzymes involved in assembly of the highly conserved LPS core in H. pylori results in mutants that are unable to colonize mice, typifying the essential nature of most PAMPs ( 37 , 38 ). Furthermore, despite the fact that waaC was the first LPS biosynthesis gene identified in H. pylori , attempts to generate deletion mutants proved unsuccessful ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the crystal structure of H. pylori HldD revealed that both the substrate binding site and the overall structure were highly similar to those of the HldD of E. coli , suggesting a conserved enzymatic function ( 36 ). It has also been shown that deletion of several enzymes involved in assembly of the highly conserved LPS core in H. pylori results in mutants that are unable to colonize mice, typifying the essential nature of most PAMPs ( 37 , 38 ). Furthermore, despite the fact that waaC was the first LPS biosynthesis gene identified in H. pylori , attempts to generate deletion mutants proved unsuccessful ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…ADP- l , d -heptose and ADP- d , d -heptose are incorporated into the highly conserved core structure of H. pylori LPS, which consists of a hexa-saccharide (glucose—galactose- d , d -heptose [Hep III]— l , d -heptose [Hep II]— l , d -heptose [Hep I]—KDO). The variable O-antigen is directly attached to the Hep III molecule ( 37 ). The LPS molecule is assembled in the bacterial cytosol, transported across the periplasm, and flipped across the outer bacterial membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assembly of O-antigen polysaccharides has so far been described to take place in four different ways, viz., (i) the synthasedependent pathway present in Salmonella enterica O:54 in which a D-ManpNAc homopolymer is formed having alternating β-(1 3)and β-(1 4)-linkages (27), (ii) the ATP-binding cassette (ABC)transporter-dependent pathway present e.g. in some E. coli in which the chain elongation takes place in the cytoplasm on a primer-adaptor trisaccharide and is terminated through the addition of a non-reducing terminal modification (28), (iii) the Wzk-dependent pathway present in H. pylori in which the Lewis-antigen containing O-antigen (29) assembled in the cytoplasm is transferred to the periplasm by a flippase that is a homologue of N-glycosylation proteins in other bacteria (30,31), and (iv) the Wzx/Wzy-dependent pathway in which an oligosaccharide is built on the cytoplasmic side of the IM and then flipped by Wzx to the periplasm where it is polymerized by the action of Wzy (32); this pathway is present in the majority of E. coli serogroups. All four pathways of formation of O-antigen polysaccharides lead to sufficiently long polymers such that a repetitive structure can be identified, which is referred to as the repeating unit (RU) of the O-antigen.…”
Section: B Biosynthesis Pathways and Sugar Donorsmentioning
confidence: 99%